2007
DOI: 10.1016/j.brainresrev.2007.06.006
|View full text |Cite
|
Sign up to set email alerts
|

“Listening” and “talking” to neurons: Implications of immune activation for pain control and increasing the efficacy of opioids

Abstract: It is recently become clear that activated immune cells and immune-like glial cells can dramatically alter neuronal function. By increasing neuronal excitability, these non-neuronal cells are now implicated in the creation and maintenance of pathological pain, such as occurs in response to peripheral nerve injury. Such effects are exerted at multiple sites along the pain pathway, including at peripheral nerves, dorsal root ganglia, and spinal cord. In addition, activated glial cells are now recognized as disru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
138
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(143 citation statements)
references
References 263 publications
(326 reference statements)
3
138
0
2
Order By: Relevance
“…We found that both cytokines enhanced synaptic AMPAR-and/or NMDAR-mediated currents in lamina I neurons and induced LTP in a significant proportion of neurons. Amplification of synaptic strength between C-fibers and lamina I (present study) and lamina II neurons (Kawasaki et al, 2008;Park et al, 2011;Zhang et al, 2011) by IL-1␤ and/or TNF-␣ are potential mechanisms underlying the hyperalgesia that can be evoked by either of these cytokines (Watkins et al, 1994;Sung et al, 2004;Kawasaki et al, 2008).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…We found that both cytokines enhanced synaptic AMPAR-and/or NMDAR-mediated currents in lamina I neurons and induced LTP in a significant proportion of neurons. Amplification of synaptic strength between C-fibers and lamina I (present study) and lamina II neurons (Kawasaki et al, 2008;Park et al, 2011;Zhang et al, 2011) by IL-1␤ and/or TNF-␣ are potential mechanisms underlying the hyperalgesia that can be evoked by either of these cytokines (Watkins et al, 1994;Sung et al, 2004;Kawasaki et al, 2008).…”
Section: Discussionmentioning
confidence: 58%
“…Cytokine receptors may be expressed on neurons and/or glial cells (Li et al, 2005;Xu et al, 2006;Guo et al, 2007;Wei et al, 2008;. Therefore, cytokines do not necessarily modify synaptic strength directly by binding to presynaptic and/or postsynaptic receptors.…”
Section: Introductionmentioning
confidence: 99%
“…After a stimulus has resolved, experimental evidence suggests microglia remain "primed", entering a sensitised state in which they do not actively produce pro-inflammatory substances, yet they over-respond to subsequent stimuli, increasing pro-inflammatory cytokine release and exaggerating pain. [94][95][96] Activation of spinal microglia and astrocytes has been demonstrated in virtually every clinically relevant animal model of an enhanced pain state 88 with similar results reported for trigeminal pain models. 97 Moreover, glial-attenuating pharmacological interventions are able to block the phenotypic transformation of glial cells into the activated state and prevent both allodynia and hyperalgesia across a diverse range of pre-clinical pathological pain models.…”
Section: Neuroimmune Interactions In Painmentioning
confidence: 62%
“…[85][86][87] It is likely that other glial cell types are also involved in pain facilitation, however research to date has focused upon astrocytes and microglia, as they are the most amenable to study. 88,89 An incontrovertible wealth of pre-clinical data show when exposed to stimuli, such as central nervous system (CNS) trauma, ischaemia, neurodegeneration or the immunological components of pathogens, microglial cells rapidly become 'activated', i.e. they develop an ability to perform a function beyond that which they are able to perform in the baseline state.…”
Section: Neuroimmune Interactions In Painmentioning
confidence: 99%
“…Current studies provide evidence of bidirectional influence between neurons and these glial cells (Fields and Stevens-Graham, 2002;Nave and Trapp, 2008). Indeed, glial cells of the central nervous system are now viewed as a crucial third element of the synapse, and may be similarly important in the peripheral nervous system (Vesce et al, 2001;Watkins et al, 2007;Filippo et al, 2008). Given the heterogeneous nature of a typical preparation of DRG cells, this study aimed to identify whether the PTX-dependent neurite retraction response was specific to any one of the three subpopulations of neurons and to determine whether the non-neuronal cells were involved in regulating this response.…”
Section: Introductionmentioning
confidence: 99%